2014
DOI: 10.1111/1475-6773.12186
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Practices and HCAHPS: Does Rewarding and Supporting Workplace Compassion Influence Patient Perceptions?

Abstract: Objective To examine the benefits of compassion practices on two indicators of patient perceptions of care quality—the Hospital Consumer Assessment of Healthcare Providers and systems (HCAHPS) overall hospital rating and likelihood of recommending. Study Setting Two hundred sixty‐nine nonfederal acute care U.S. hospitals. Study Design Cross‐sectional study. Data Collection Surveys collected from top‐level hospital executives. Publicly reported HCAHPS data from October 2012 release. Principal Findings Compassio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 37 publications
1
61
0
1
Order By: Relevance
“…Our research identified one instrument that was developed to measure compassion as an emotion in healthcare providers [35,36], three instruments that were created to measure healthcare providers' ability to provide compassionate care [34,37,38], one study that measured compassion in association with the patient care experience [39] and three studies that evaluated compassion as indicators of educator instructional performance and quality, or as attributes in residents, fellows and medical/nursing students [40][41][42]. While we report on several measures of compassion, each is associated with significant limitations that warrant careful consideration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our research identified one instrument that was developed to measure compassion as an emotion in healthcare providers [35,36], three instruments that were created to measure healthcare providers' ability to provide compassionate care [34,37,38], one study that measured compassion in association with the patient care experience [39] and three studies that evaluated compassion as indicators of educator instructional performance and quality, or as attributes in residents, fellows and medical/nursing students [40][41][42]. While we report on several measures of compassion, each is associated with significant limitations that warrant careful consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies described patient-report instruments to examine the importance of physician and nurse compassion in different patient populations [35][36][37][38]. One study that measured organizational support for compassionate care was also included [39]. Three studies measured compassion in educational institutions, either as indicators of educator instructional performance and quality, or as attributes in residents, fellows or medical/nursing students [40][41][42].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…HCAHPS performance, the return on these projects' investments is readily calculated (e.g., Weech-Maldonado et al 2012;Merlino and Raman 2013;Petrullo et al 2013;McClelland and Vogus 2014).…”
mentioning
confidence: 99%